FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA PERAWAT RUMAH SAKIT PABATU DI SERDANG BERDAGAI - Sonny Pramudya Taringan (Program Studi Ilmu Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Indonesia Timur, 2020)
Human resources greatly affect the differentiation and quality of service. The human resources are health workers, but these health workers certainly have limitations and diversity in achieving quality indicators of services available in hospitals. The purpose of this study was to analyze the factors influencing the performance of Pabatu hospital nurses in Serdang Berdagai. This type of research is a quantitative study with an explanatory research approach with a cross-sectional research design that was carried out at Serdang Berdagai Pabatu Hospital. The population and sample in this study were nurses who worked at the Pabatu hospital in Serdang Berdagai as many as 68 people. Results showed that training had a significant effect on nurse performance (p = 0.003), leadership variables had a significant effect on nurse performance (p = 0.001), compensation variables had a significant effect on nurse performance (p = 0.020) and the work environment variable had a significant effect on nurse performance (p = 0.041). In the training factor there is an opportunity to improve nurse performance by 4,019 times, in the leadership factor, it is likely to increase nurse performance by 5,012 times, In the compensation factor it has the opportunity to improve the nurse's performance by 7,279 times, in the work environment factor has the opportunity to improve the nurse's performance by 3,256 times. The conclusion that there is an influence of training, leadership, work environment compensation factors on nurse performance. It is recommended that nurses receive training in accordance with the duties of each assignment room.